Pemenuhan Kebutuhan Informasi Generasi Z di Universitas Mulawarman Melalui Instagram @Kaltimfolks Sebagai Citizen Journalism - Alda Puspita Dewi; Nurliah Nurliah; Dony Kristian; Harry Isra Muhammad (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
The rise of new media such as instagram has transformed how generation Z seeks information as a digital natives. This study aims to analyze how the informational needs of Generation Z at Mulawarman University are met through the Instagram account @Kaltimfolks, a user platform that are identified as a citizen journalism. The study employs a descriptive qualitative approach using purposive sampling. Data collection was performed through interviews, observation, and documentation. This study analyzes the findings based on the uses & gratification 2.0 theory proposed by Sundar and Limperos (2013) through the MAIN model. The results indicate that @Kaltimfolks effectively meets generation Z’s information needs through the four MAIN model components: modality, agency, interactivity, and navigability. The audience does not merely passively consume information but actively engages through various forms of interaction facilitated by @Kaltimfolks. This study also highlights that the new media ecosystem presents more complex needs that cannot be fully explained by classical uses & gratification theory.